2017
DOI: 10.1038/nature21077
|View full text |Cite
|
Sign up to set email alerts
|

MFN1 structures reveal nucleotide-triggered dimerization critical for mitochondrial fusion

Abstract: Mitochondria are double-membrane organelles with varying shapes influenced by metabolic conditions, developmental stage, and environmental stimuli1–4. Their dynamic morphology is realized through regulated and balanced fusion and fission processes5, 6. Fusion is crucial for the health and physiological functions of mitochondria, including complementation of damaged mitochondrial DNAs and maintenance of membrane potential6–8. Mitofusins (Mfns) are dynamin-related GTPases essential for mitochondrial fusion9, 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
329
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(368 citation statements)
references
References 51 publications
22
329
4
3
Order By: Relevance
“…Both the GTPase and HR2 domains are crucial for the fusion process as mutations in these domains either prevent GTPase activity and thereby eliminate fusogenic activity, or disrupt the dimeric antiparallel coiled-coil structure and abolish membrane tethering (Qi et al, 2016). Consistent with this, Cao et al (2017) observed that dimerization of the GTPase domains is mediated by a conserved GTPase domain interface across the nucleotide binding site, resulting in activation of GTPase activity. Preventing dimerization of the GTPase domain led to impaired fusogenic activity of Mfn1, suggesting a crucial role for the G-interface in mitochondrial fusion (Cao et al, 2017).…”
Section: Genomic and Protein Organization Of The Mitofusinssupporting
confidence: 68%
See 3 more Smart Citations
“…Both the GTPase and HR2 domains are crucial for the fusion process as mutations in these domains either prevent GTPase activity and thereby eliminate fusogenic activity, or disrupt the dimeric antiparallel coiled-coil structure and abolish membrane tethering (Qi et al, 2016). Consistent with this, Cao et al (2017) observed that dimerization of the GTPase domains is mediated by a conserved GTPase domain interface across the nucleotide binding site, resulting in activation of GTPase activity. Preventing dimerization of the GTPase domain led to impaired fusogenic activity of Mfn1, suggesting a crucial role for the G-interface in mitochondrial fusion (Cao et al, 2017).…”
Section: Genomic and Protein Organization Of The Mitofusinssupporting
confidence: 68%
“…Consistent with this, Cao et al (2017) observed that dimerization of the GTPase domains is mediated by a conserved GTPase domain interface across the nucleotide binding site, resulting in activation of GTPase activity. Preventing dimerization of the GTPase domain led to impaired fusogenic activity of Mfn1, suggesting a crucial role for the G-interface in mitochondrial fusion (Cao et al, 2017).…”
Section: Genomic and Protein Organization Of The Mitofusinssupporting
confidence: 65%
See 2 more Smart Citations
“…The pathogenicity of several missense variants at the same location including that found in the participant family were respectively predicted using online tools PolyPhen-2 (), Scale-Invariant Feature Transform (SIFT; ), MutationTaster () and M-CAP (). The three-dimensional structures of normal and mutant mitofusin 2 were generated by homology modeling using SWISS-MODEL () (12). The structure of mitofusin 2 was examined with the crystal structure of the truncated mitofusin 1 structure (pdb 5GOM).…”
Section: Methodsmentioning
confidence: 99%